HOW INCLUSIVE IS AN INCLUSIVE COURT? The Practice of an Islamic Court in Malang, Indonesia - Maftuhin, Arif (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2026)
Ensuring the rights of individuals with disabilities continues to be a major challenge across various sectors in Indonesia. A key concern is safeguarding these rights within the judicial system, which is crucial for access to justice. Previous research has highlighted a range of paradigmatic, policy, and practical obstacles that often prevent individuals with disabilities from achieving fair access to the judiciary. This study investigates these challenges within the context of an Islamic court in Malang Regency, Indonesia. Through observations and interviews with court personnel and individuals with disabilities, it is evident that the Malang Regency Religious Court has made strides toward inclusivity. Efforts have been focused primarily on physical accessibility improvements, such as installing guiding blocks for the visually impaired, designating drop zones and parking spaces for disabled persons, providing ramps to access courtrooms, offering assistive devices, and issuing priority service cards. However, non-physical barriers still impede the development of a fully inclusive Islamic court. These include prevailing disability paradigms, cultural issues, and mental obstacles. [Pemenuhan hak-hak penyandang disabilitas masih menjadi tantangan besar di berbagai sektor di Indonesia. Salah satu isu krusial adalah perlindungan hak-hak tersebut dalam sistem peradilan, mengingat pentingnya akses terhadap keadilan. Penelitian-penelitian sebelumnya menunjukkan adanya berbagai hambatan paradigmatik, kebijakan, dan praktik yang kerap menghalangi penyandang disabilitas untuk memperoleh akses yang adil terhadap lembaga peradilan. Studi ini mengkaji tantangan tersebut dalam konteks pengadilan agama di Kabupaten Malang, Indonesia. Berdasarkan hasil observasi dan wawancara dengan aparatur pengadilan serta penyandang disabilitas, ditemukan bahwa Pengadilan Agama Kabupaten Malang telah melakukan sejumlah upaya menuju inklusivitas. Upaya tersebut terutama difokuskan pada peningkatan aksesibilitas fisik, seperti pemasangan guiding block bagi penyandang disabilitas netra, penyediaan drop zone dan area parkir khusus bagi penyandang disabilitas, penyediaan ramp untuk akses menuju ruang sidang, pemberian alat bantu, serta penerbitan kartu layanan prioritas. Namun demikian, hambatan nonfisik masih menghalangi terwujudnya pengadilan agama yang sepenuhnya inklusif. Hambatan tersebut meliputi paradigma disabilitas yang masih berkembang, faktor budaya, serta hambatan mental atau sikap aparatur dan lingkungan peradilan.]